Hubungan antara Kualitas Pelayanan Barista Tuna Rungu Wicara dengan Kepuasan Konsumen - Tania Nurfitria; Anne Ratnasari (UNISBA Press, 2024)
Abstract. Culture shock in an individual occurs because a person enters a new culture to himself which makes him have to adjust to an environment, place, and habits that are different from his previous life. Students of Communication Science at the Islamic University of Bandung class of 2021 experience Culture Shock towards changes in learning from online to offline. This change affects the adaptation of overseas students, because they have to adjust to a new environment, language, and culture. The 2021 batch of Communication Science students at the Islamic University of Bandung experienced crocodile shock because they had to overcome anxiety and anxiety in direct social interaction. The purpose of this research is to examine the adaptation process of overseas students of the Faculty of Communication Science, Islamic University of Bandung class of 2021 after experiencing changes from online to offline learning. The research method in this study uses a qualitative method with a case study approach using the theory of culture shock from Samovar (2010). Then, data sources are obtained through interviews, observation, and documentation with Communication Science Students of the Islamic University of Bandung class of 2021. Data analysis will be carried out using data reduction analysis techniques, data presentation, and conclusion drawing. The results showed that in the adaptation process, overseas students felt several phases such as Honeymoon Phase, Crisis Phase, Adjusment Phase to Adaptation Phase. Culture shock barriers arise from several internal and external factors such as external factors in the form of environmental changes, to internal in the form of differences in perceptions and habits. The reasons for culture shock are differences in language, culture, habits, perceptions, communication and relationships that they felt were foreign before. Abstrak. Pertumbuhan ekonomi terjadi begitu cepat. Manusia dituntut melakukan kegiatan berbisnis karena kebutuhan yang meningkat. Salah satu bisnis UMKM yang sangat berkembang pesan saat ini ialah bisnis kopi. Dari berangamnya coffee shop yang ada, Serona Coffee Bintaro merupakan coffee shop yang memiliki keunikan karena mempekerjakan barista difabel. Menjaga komunikasi pemasaran dan mempertahankan layanan dengan konsisten menjadikan konsumen puas pada layanan Serona Coffee Bintaro. Tujuan Penelitian ini untuk mengetahui adanya hubungan antara kualitas pelayanan barista difabel dengan kepuasan konsumen Serona Coffee Bintaro yang terdiri dari 5 macam indikator yang akan dibahas yaitu tangibles, reliability, responsiveness, assurance dan empathy. Penelitian ini menggunakan metode penelitian kuantitatif dengan pendekatan korelasional. Teknik pengumpulan data berupa kuesioner, wawancara sebagai data pendukung dan kepustakaan dengan teknik analisis data menggunakan skala likert. Pengambilan sampel dalam penelitian ini menggunakan teknik simple random sampling dengan menyebarkan kuesioner kepada konsumen Serona Coffee Bintaro yang berjumlah sebanyak 98 responden. Metode analisis yang digunakan adalah analisis deskriptif dan analisis rank spearman. Berdasarkan hasil penelitian yang didapatkan terdapat hubungan antara tangibles terhadap kepuasan konsumen, reliability terhadap kepuasan konsumen, responsiviness terhadap kepuasan konsumen, assurance terhadap kepuasan konsumen dan emphaty terhadap kepuasan konsumen. Keseluruhan hasil analisis rank spearman menyatakan seluruh dimensi variabel kualitas pelayanan berkorelasi searah dan positif terhadap variabel kepuasan konsumen. Penelitian selanjutnya dapat mencakup responden lebih banyak dengan objek penelitian yang berbeda.